“TEACHING” AND “LEARNING”: FEATURES OF NATIONAL TERMINOLOGY - L. S. Grebnev, (Высшее образование в России)
The article examines the difficulties of an adequate translation into Russian of the term “learning” as the key one in the Bologna process. The absence of unambiguous translation affects the perception of the contents of the cycle of articles by V.I. Baidenko and N.A. Selezneva.